2006
DOI: 10.1038/sj.ki.5001655
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of dexamethasone on human podocytes

Abstract: Glucocorticoids are widely used in the treatment of human glomerular diseases, but their mode of action is poorly understood particularly in steroid-sensitive nephrotic syndrome, which is most common in childhood and is characterized by a lack of inflammation in the kidney. The podocyte is a key cell in the glomerulus in health and disease: until recently, human podocytes have been difficult to study in vitro. We have developed a conditionally immortalized human podocyte cell line transfected with a temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 37 publications
4
140
0
1
Order By: Relevance
“…In addition to its immunomodulatory effect, corticosteroid directly affects the gene expression of podocytes (31). Dexamethasone promotes the expression of nephrin and other proteinuria-associated factors in human podocytes in a dose-dependent fashion within a range corresponding to the intravenous mPSL therapy used in this study (31). Thus, the effectiveness of mPSL +PSL in this study may be partly ascribed to the higher initial dose of corticosteroid, which normalized podocyte function more strongly.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition to its immunomodulatory effect, corticosteroid directly affects the gene expression of podocytes (31). Dexamethasone promotes the expression of nephrin and other proteinuria-associated factors in human podocytes in a dose-dependent fashion within a range corresponding to the intravenous mPSL therapy used in this study (31). Thus, the effectiveness of mPSL +PSL in this study may be partly ascribed to the higher initial dose of corticosteroid, which normalized podocyte function more strongly.…”
Section: Discussionmentioning
confidence: 70%
“…Although the precise MCD pathogenesis remains unknown, immunologic perturbations, especially in T cells (26), and subsequent injury to glomerular podocytes (27), including reduced expression of nephrin (28)(29)(30), lead to massive proteinuria in MCD. In addition to its immunomodulatory effect, corticosteroid directly affects the gene expression of podocytes (31). Dexamethasone promotes the expression of nephrin and other proteinuria-associated factors in human podocytes in a dose-dependent fashion within a range corresponding to the intravenous mPSL therapy used in this study (31).…”
Section: Discussionmentioning
confidence: 99%
“…For APOL1 FSGS, response rates to glucocorticoids are probably similar to those seen in primary FSGS, although the data are limited (83). The mechanism by which glucocorticoids affect podocytes are poorly understood; these agents are known to have direct effects on cultured podocytes (132). Recently, it has been suggested that these agents can expand the population of myeloid-derived suppressor cells that downregulate T cell function (133).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Recent reports indicate that dexamethasone induces transcriptional activation of nephrin and enhances nephrin expression in vitro, suggesting that this mechanism could be involved in the steroid response observed in minimal change disease. 24 To test the hypothesis that enhanced podocyte VEGF causes proteinuria in developing mice by disrupting nephrin signaling we developed an inducible mouse model of moderate podocyte VEGF 164 overexpression. Here we examined the phenotypes resulting from podocyte VEGF 164 excess at two developmental stages: during organogenesis and in the newborn mouse.…”
mentioning
confidence: 99%